Rancang Bangun Antena Unidirectional Ultra-Wideband dengan Desain Fork-Shaped Tuning Stub menggunakan Bahan Dielektrik Fr-4 - Yusron Tri Huda; Tommi Hariyadi; Budi Mulyanti (Universitas Pendidikan Indonesia, 2016)
In this paper, Ultra Wide Band (UWB) mictrostrip antenna was designed for through-wall-imaging radar. The simulation was carried out using CST Studio. The FR-4 substrate with dielectric constant of 4,3 and thickbess of 1,6 mm is used in this project. The simulation result confirm that antenna have 4,8 GHz of bandwidth from 4,2 to 9 GHz with -10dB return loss. The measured result confirm that antenna have 5 GHz bandwidth from 3,8 to 8,8 GHz with a same return loss.